Investigation of Polyvinyl Alcohol/Clove Essential Oil Property as a Repellent against Corn Leaf Aphids (Rhopalosiphum Maidis F.) - BIN ROSTAM, MUHAMMAD SAFIUDDIN; BIN YUNOS, MUHAMAD ZAINI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Clove essential oil have become immensely popular over the past decade as it is high in antioxidants, antiviral and antifungal properties. This research is to study the ability of a polymer based product which were made from polyvinyl alcohol (PVA) and clove essential oil (CEO) whether it can repel the presence of insects towards certain crop plants or not. The objective of conducting this research is to study the effect of clove essential oil on mechanical properties of PVA as well as to evaluate the aphid behaviour of repellency towards the prepared materials which the samples were prepared through casting method. The casting process were done by dissolving CEO in 100 ml PVA solution at 80°C and then were left dry at ambient temperature. The analysis was conducted through tensile test, solubility, biodegradability as well as repellency test. From the results obtained, it stated that for tensile test, the lower the oil concentration in the prepared sample, the higher the average length different produce thus indicates that it has a higher tensile strength. As for solubility test, it is shown that, the sample that has the right ratio of PVA composition and oil concentration, gives a better structural advantages as it has both tensile strength and hydrophobic properties and thus will help the sample to maintain their shape better during being immersed in water. The same concept applied for biodegradability test, the result stated that, the sample that has the right ratio of PVA composition and oil concentration, help the sample to maintain their shape and prevent them from degrades better. Lastly, for repellency test it stated that, the higher the oil concentration in the prepared sample, the higher the percentage of repellency and thus the longer the repellency process can withstand.